2012
DOI: 10.1186/1748-717x-7-64
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cytokine protein levels in oral secretions in patients undergoing radiotherapy for head and neck malignancies

Abstract: BackgroundCytokines may be elevated in tumor and normal tissues following irradiation. Cytokine expression in these tissues may predict for toxicity or tumor control. The purpose of this pilot study was to determine the feasibility of measuring local salivary cytokine levels using buccal sponges in patients receiving chemo-radiation for head and neck malignancies.Patients and methods11 patients with epithelial malignancies of the head and neck were recruiting to this study. All patients received radiotherapy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 12 publications
5
55
0
1
Order By: Relevance
“…Previous studies suggest that RT-induced changes in pro-inflammatory cytokines and growth factors may contribute to normal tissue toxicities (11, 12). Our current data provide new evidence that the inflammatory biomarker, plasma CRP levels are associated with RT-induced EASRs in breast cancer patients undergoing RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggest that RT-induced changes in pro-inflammatory cytokines and growth factors may contribute to normal tissue toxicities (11, 12). Our current data provide new evidence that the inflammatory biomarker, plasma CRP levels are associated with RT-induced EASRs in breast cancer patients undergoing RT.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation may play critical roles in RT-induced EASRs and previous studies showed that RT induces changes in pro-inflammatory (IL-1α, IL-4, IL-2, IL-6, IL-8, IL-10, TNF-α, IFN-γ), pro-fibrotic (TGF-β1), pro-angiogenic (VEGF) and stem cell mobilizing (GM-CSF) cytokines and growth factors that may contribute to normal tissue toxicities or tumor control (11, 12). In addition, an inflammatory biomarker, C-reactive protein (CRP) has been associated with elevated risk for vascular atherosclerosis, insulin resistance, type 2 diabetes mellitus, and cancer (1315).…”
Section: Introductionmentioning
confidence: 95%
“…Deficiency of TNF-α in a lung injury model was sufficient to prevent symptoms of radiation pneumonitis 70 . TNF-α has also been implicated in radiation mucositis, enteritis, and dermatitis 7175 . The clinical availability of agents targeting TNF-α to treat rheumatologic disorders provides a unique opportunity for clinical translation, and will likely enhance investigation into this molecule and its pathway.…”
Section: Tgf-β and Tnf-α Signaling In Normal Tissue Toxicitymentioning
confidence: 99%
“…Cytokines are prevalent within the affected tissue and are also detected in peripheral blood 5 . Studies have shown a significant increase in the levels of pro-inflammatory cytokines during chemotherapy and / or radiotherapy of head and neck, such as TNF-α 19,20 and IL-6 12,19,21 .…”
Section: Chemical Mediators That Enhance Oral Mucositismentioning
confidence: 99%